2022
DOI: 10.3390/d14020067
|View full text |Cite
|
Sign up to set email alerts
|

Study of Rhizosphere Microbial Community Structures of Asian Wild and Cultivated Rice Showed That Cultivated Rice Had Decreased and Enriched Some Functional Microorganisms in the Process of Domestication

Abstract: Asian cultivated rice (Oryza sativa L.), domesticated from Asian wild rice, is a staple food crop for populations around the world. Asian cultivated rice has undergone physiological changes in the process of its evolution from Asian wild rice, and the closely related rhizosphere microorganisms may have changed in the process of plant domestication. However, the rhizosphere microorganisms of different Asian wild rice species and their related indica and japonica cultivated rice have not yet been illustrated cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Although there was little difference between Pathotrophs in the wild and cultivated species, the Soil Saprotroph of LCT2 was significantly higher than that of LZT2, and the Mixed Saprotroph of LCT1 was significantly higher than that of LZT1. These Saprotrophs are prone to enrichment in decaying and diseased plants and are more prone to causing plant diseases ( Zhang et al., 2022 ). Rhizosphere soil fungi and bacteria exhibited similar patterns, compared to cultivated varieties, wild beet ( Beta vulgaris ssp.)…”
Section: Discussionmentioning
confidence: 99%
“…Although there was little difference between Pathotrophs in the wild and cultivated species, the Soil Saprotroph of LCT2 was significantly higher than that of LZT2, and the Mixed Saprotroph of LCT1 was significantly higher than that of LZT1. These Saprotrophs are prone to enrichment in decaying and diseased plants and are more prone to causing plant diseases ( Zhang et al., 2022 ). Rhizosphere soil fungi and bacteria exhibited similar patterns, compared to cultivated varieties, wild beet ( Beta vulgaris ssp.)…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, plant genotype has a significant effect on rhizosphere microbial communities [ 37 ] and the artificial selection of plant host genomes during domestication could affect their interaction with AMF or other soil microorganisms [ 38 ]. Whether modern crop varieties lost the genes required to benefit from mutualistic interactions will be interesting to study using large sequence databases [ 33 ].…”
Section: Rice Domestication and Amsmentioning
confidence: 99%
“…However, recent studies revealed that during the process of domestication, crop plants may not only lose genetic diversity, but also lose some host-specific microbes, which may be recruited by the distinct traits of wild relatives ( 14 , 19 ). So far, the rhizosphere microbial communities of wild rice have been preliminarily characterized ( 20 ), while the phyllosphere microbiome of wild rice has rarely been documented. Therefore, it is crucial to gain a better understanding of the phyllosphere microbial community of wild rice, which is also essential to modulate its activity for the benefit of rice production.…”
Section: Introductionmentioning
confidence: 99%